Coping flexibility and eudaimonic well‐being in university students. Issue 4 (31st May 2018) - Freire, Carlos; Ferradás, María Del Mar; Núñez, José Carlos; Valle, Antonio
Abstract : Despite the growing interest in the relationship between coping strategies and eudaimonic well‐being, few studies have examined this issue from the perspective of coping flexibility. Therefore, the present study aimed to: (1) identify approach coping profiles in the university context and (2) analyze the differences between these profiles in terms of eudaimonic well‐being. A prospective ex post facto design was used and 1, 402 university students were selected through convenience sampling. Data were collected using validated self‐reported instruments. A latent profile analysis was conducted to identify the participants' coping profiles. The relationship between profiles and eudaimonic well‐being was determined using a multivariate analysis of covariance (MANCOVA), with gender, age, and university degree as covariates. Six student profiles were identified based on the degree to which they combined positive reappraisal, support seeking, and planning strategies. The profiles that involved the use of these three strategies to a greater extent experienced more eudaimonic well‐being, and vice versa. To analyze the impact of coping on eudaimonic well‐being, it is necessary to consider students' ability to combine different approach coping strategies.